Enhancing Brand Awareness Through Visual Branding: A Case Study of Pet&Co - Aginsa, Meidina Puteri; Wulansari, Amilia (Integrasi Sains Media, 2024)
Effective visual branding is essential for boosting brand awareness in Indonesia's rapidly growing pet care industry. This study investigates the challenges faced by Pet&Co, a new pet supplement brand, in enhancing its social media presence and brand recognition. Despite its innovative product, 'Colla Blend,' Pet&Co struggles with low engagement and brand visibility, particularly on Instagram. Through a comprehensive research approach that includes consumer feedback, expert opinions, and a literature review, the study identifies key factors for improving visual branding: logo design, colour scheme, typography, size, shape, and imagery. Proposed strategies to address these branding issues involve enhancing social media marketing, expanding the e-commerce presence, collaborating with pet shops and influencers, targeting B2B markets, and investing in product innovation. These strategies aim to rectify current branding deficiencies and strengthen Pet&Co's market presence. The findings suggest that a multi-platform exposure strategy, combined with dynamic and engaging content, will significantly improve brand visibility and consumer interaction in the competitive pet care industry.